V‐loc™ capable of grasping surrounding tissue causes obstruction at the jejunojejunostomy after Roux‐en‐Y laparoscopic gastric bypass. Issue 2 (May 2015) - Oor, Jelmer; de Castro, Steve; van Wagensveld, Bart
Abstract: Because of the increasing number of morbidly obese patients, laparoscopic Roux‐en‐Y gastric bypass surgery is increasingly being performed to treat these patients and achieve sustained weight loss. Postoperative abdominal symptoms suggestive of impaired gastrointestinal passage are a diagnostic challenge after Roux‐en‐Y gastric bypass. Here, we present the case of a V‐loc™‐induced obstruction at the jejunojejunostomy caused by the ability of the V‐loc suture to grasp surrounding tissue that required re‐laparoscopy. To our knowledge, this specific type of postoperative complication after Roux‐en‐Y gastric bypass has not been described previously.